2023
DOI: 10.1039/d2se01678h
|View full text |Cite
|
Sign up to set email alerts
|

All-blade-coated flexible perovskite solar cells & modules processed in air from a sustainable dimethyl sulfoxide (DMSO)-based solvent system

Abstract: Flexible Perovskite solar cells have been considered promising candidates for novel applications that require a high power-to-weight ratio. However, the scalable and ambient air deposition of efficient devices are still...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The minimodules we fabricated consist of two cells with a total active area of 2.9 cm 2 with the PET/ITO/SnO 2 /KCl/FAPbBr 3 /PTAA/ITO device architecture. The optimization of the laser parameters, including interconnection width and laser fluences, has been carried out starting from a previous optimization procedure: a matrix of laser power as a function of pulse densities has been implemented for each etching process, moving around the starting values optimized in our previous studies combining semitransparent and flexible substrates. , We minimized the losses on the P2 process by applying three couple of lines by differing by 200 pulse density each, keeping the power density constant for all cases: especially for the flexible substrate, the presence of valleys and hills at the microscopic level is unavoidable at the time of marking the lines, causing defocusing; therefore, the use of slightly different parameters helps to homogenize the ablation, fundamental to reduce losses at the interconnections . By reducing the scribe width and optimizing laser parameters, we attained 155 μm interconnection width (Figure S7), resulting in a geometrical fill factor of 97.83%.…”
Section: Resultsmentioning
confidence: 99%
“…The minimodules we fabricated consist of two cells with a total active area of 2.9 cm 2 with the PET/ITO/SnO 2 /KCl/FAPbBr 3 /PTAA/ITO device architecture. The optimization of the laser parameters, including interconnection width and laser fluences, has been carried out starting from a previous optimization procedure: a matrix of laser power as a function of pulse densities has been implemented for each etching process, moving around the starting values optimized in our previous studies combining semitransparent and flexible substrates. , We minimized the losses on the P2 process by applying three couple of lines by differing by 200 pulse density each, keeping the power density constant for all cases: especially for the flexible substrate, the presence of valleys and hills at the microscopic level is unavoidable at the time of marking the lines, causing defocusing; therefore, the use of slightly different parameters helps to homogenize the ablation, fundamental to reduce losses at the interconnections . By reducing the scribe width and optimizing laser parameters, we attained 155 μm interconnection width (Figure S7), resulting in a geometrical fill factor of 97.83%.…”
Section: Resultsmentioning
confidence: 99%
“…84,93,115 Jafarzadeh et al used a two-step blade coating technique to deposit perovskite using DMSO as the solvent for the rst step. 116 They demonstrated that gas quenching in combination with additive engineering enables the deposition of perovskite on exible substrates under ambient conditions without the usage of high deposition temperature. The all-blade coated exible perovskite solar cells delivered 14% PCE.…”
Section: Non-toxic Solvents Which Can Be Used Purementioning
confidence: 99%